Exploring the Assessment Practices That Shape Learner Autonomy in Language Education - Pournaderi, Neda; Khoshkar, Shahram (Assessment and Practice in Educational Sciences, 2024)
This study aims to explore the assessment practices that shape learner autonomy in language education, focusing on the perceptions of teachers, curriculum designers, and administrators in Tehran. A qualitative research design was employed, involving semi-structured interviews with 28 participants selected purposively from language education institutions in Tehran. Data collection continued until theoretical saturation was achieved. Interviews were audio-recorded, transcribed verbatim, and analyzed using thematic analysis with the assistance of NVivo software to identify key themes and patterns related to assessment and learner autonomy. Three main themes emerged from the analysis: Assessment Design for Autonomy, Teacher Practices Facilitating Autonomy, and Learner Engagement and Autonomy. Formative feedback, self-assessment integration, authentic tasks, transparent criteria, learner choice, and continuous assessment were identified as critical design elements supporting autonomy. Teachers played a pivotal role by co-creating goals, fostering dialogic assessment, promoting reflection, encouraging peer assessment, and building trust to empower learners. Learners demonstrated autonomy through intrinsic motivation, self-regulation skills, active engagement with feedback, peer collaboration, and emotional resilience. Barriers such as cultural expectations, fear of failure, and teacher dependence were also acknowledged as challenges to autonomy development. Assessment practices significantly influence learner autonomy in language education by providing structures and supports that empower learners to take control of their learning. Formative, authentic, and learner-centered assessment approaches, combined with supportive teacher mediation, facilitate autonomy development. However, contextual factors and learner readiness must be considered to effectively implement autonomy-supportive assessments. The study recommends embedding formative feedback, self- and peer-assessment, and authentic tasks in language curricula while fostering trusting, dialogic teacher-student relationships to maximize learner autonomy.